Distribution and additive partitioning of diversity in freshwater mollusk communities in Southern Brazilian streams - Alcemar R. Martello (Revista de Biología Tropical, 2014)
Additive partitioning of species diversity is a promising approach for analyzing patterns of diversity in mollusk communities, especially their spatial distribution. Our aims were to assess the distribution of mollusk communities in Southern Brazilian streams, and to evaluate the partitioning of community diversity at different spatial scales. The study was carried out in the lower course of the Toropi River, one of the main tributaries of the Ibicuí River Basin, in Southern Brazil. Four microbasins were considered: Sertão da Mata, Ribeirão, Tororaipi and Chiniquá, and sampling were undertaken in autumn, April and May 2009. Six sites were sampled in each stream: two in 1st-order segments, two in 2nd-order segments, and two in 3rd-order segments. All species found and the community as a whole, exhibited a clumped distribution. However, the variance-to-mean ratios for the Drepanotrema kermatoides and Heleobia bertoniana were higher than those of other species, suggesting a higher degree of aggregation. The additive partitioning of the species richness showed that the observed richness at smallest scale (α=within streams) represented 20.7%, and among-streams (β1) represented 10.5% of the total richness. The richness and Shannon diversity index observed at the alpha scale, were higher than those observed at the first level of beta diversity scale (β1=among-streams). The interaction between passive dispersal, tolerance to changes in some environmental variables, abiotic factors, and clumped distribution might have determined the spatial distribution of the communities studied. The greatest variation at the larger scales of analysis, involving among-orders and among-microbasins (β2 and β3, respectively) components, was expected, considering that the increase in distance leads to greater differences in richness (higher beta diversity). In conclusion, our results showed that the clumped distribution influenced the partition of the diversity of the mollusk communities in the streams studied. Dispersal methods and tolerance to variations in abiotic factors also have important roles in determining high alpha diversity. The partitioning of diversity showed that to preserve limnetic mollusks, it is important to preserve local areas, i.e., streams. Accordingly, conservation of streams on a local scale will contribute to conservation of the entire basin and maintenance of regional diversity (gamma).